Considerations for regulation and evaluation of digital mental health technologies - Gareth Hopkin; Richard Branson; Paul Campbell; Holly Coole; Sophie Cooper; Francesca Edelmann; Mark Salmon (Digital Health)
Digital mental health technologies (DMHTs) are becoming well established within mental health services and through direct-to-consumer models. Due to their scalable nature, DMHTs may support services to bridge the gap between demand and the available workforce, particularly where existing pathways have long delays or restricted capacity. Challenges and risks associated with DMHTs also need consideration. Regulatory and health technology assessment (HTA) agencies play a key role in ensuring the potential of DMHTs is achieved and their risks are mitigated. However, the nature of DMHTs and advances in digital technology present challenges for regulation and evaluation. In this paper, we describe eight key considerations across the regulatory and HTA pathway for DMHTs. These relate to 1) intended purpose, 2) qualification and classification, 3) risk management, 4) clinical evidence, 5) resource requirements and economic evidence, 6) post-market surveillance and life cycle assessment, 7) replicability and equity, and 8) wider responsibilities. Ensuring clarity within these considerations and addressing outstanding uncertainties is necessary to ensure that the benefits of DMHTs are unlocked, while also ensuring that people have access to high quality and safe tools.